2014
DOI: 10.1016/j.jdermsci.2014.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor inhibitors selectively inhibit the expressions of human β-defensins induced by Staphylococcus epidermidis

Abstract: EGFRIs may cause cutaneous adverse effects through selectively perturbing innate immune responses induced by commensal and pathogenic bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 11 publications
3
19
0
Order By: Relevance
“…Upregulation of hBD-3 (32, 33) and downregulation of hBD-9 (32) were found in the S. aureus-infected skin (33) and in the ocular surface of the patients with bacterial keratitis (32). The hBD-3 expression was increased during the first day of the infection and then was constant within the following 2 days, as was observed in the human S. aureus-infected epidermal keratinocytes (12).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Upregulation of hBD-3 (32, 33) and downregulation of hBD-9 (32) were found in the S. aureus-infected skin (33) and in the ocular surface of the patients with bacterial keratitis (32). The hBD-3 expression was increased during the first day of the infection and then was constant within the following 2 days, as was observed in the human S. aureus-infected epidermal keratinocytes (12).…”
Section: Discussionmentioning
confidence: 66%
“…PSMα‐induced G2/M‐transition delay was related to the decrease of the antibacterial functions of the epithelial cells. The expression level of antibacterial peptides such as human β‐defensins (hBDs), the first line of defense against staphylococcal infection (12), was lower in G2/M‐phase cells compared with cells in the G1 phase. We also tested clinical human S. aureus isolates and found that cell cycle delay activity was associated with PSMα1 production.…”
mentioning
confidence: 99%
“…They include hair loss, acneiform eruption, paronychia and xerosis. EGFR inhibition enhances the production and release of proinflammatory mediators, and inhibits the production of antimicrobial peptides, resulting in the development of inflammatory papules and pustules as well as an impaired host defence function 36 37 . Interestingly, in this study, rhEGF also inhibits the expression of TLR2 and proinflammatory cytokines increased by P. acnes through the inhibition of NF-κB, which is restored by using gefitinib.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most effective early responses of the host to pathogenic insults is mediated through human β-defensins (hBD). In vitro experiments with keratinocytes or skin explants have shown that S. epidermidis or its culture supernatants can elicit high levels of hBD-2 and hBD-3 but not hBD-1 (Lai et al, 2010 ; Li et al, 2013 ; Ommori et al, 2013 ; Percoco et al, 2013 ; Park et al, 2014 ), and RNase7 and cathelicidin LL-37 in epithelial cells (Burgey et al, 2016 ). This AMP induction may be beneficial under healthy conditions to counteract more pathogenic species (Lai et al, 2010 ; Li et al, 2013 ) but can be also expected to contribute to defense in S. epidermidis superficial or ocular infections.…”
Section: Host Interaction With S Epidermidismentioning
confidence: 99%